Application of Clo3d Technology in Fashion Vocational Education in Vocational Schools: A Systematic Literature Review - Irva Widiyawati; Luhur Adi Prasetya; Anisa Permataningtyas; Didik Nurhadi; Nurul Hidayati; Muhammad Aris Ichwanto (Universitas Muhammadiyah Mataram, 2024)
This study evaluates the implementation of Clo3D technology in fashion vocational education, focusing on its benefits, challenges, and practical implications. The research employed a Systematic Literature Review (SLR) method, following PRISMA guidelines to assess relevant studies on Clo3D usage in educational contexts. Data analysis involved thematic analysis to identify key trends and outcomes from the selected literature. The results reveal that Clo3D significantly enhances student creativity, leading to a 23% increase in design diversity, and reduces material waste by 35-40%, promoting sustainable design practices. However, the research also identified critical challenges, such as inadequate infrastructure in over 60% of vocational schools and a lack of teacher preparedness, with 70% of teachers reporting insufficient training. To address these challenges, this study suggests strategic investment in technology infrastructure, comprehensive teacher training programs, gradual curriculum integration, and enhanced collaboration with the fashion industry. The novelty of this research lies in providing a concrete framework for improving Clo3D adoption in vocational education, offering insights into how schools and policymakers can bridge gaps in technology access and prepare students for industry demands.